Knowing Where It Comes From : Labeling Traditional Foods to Compete in a Global Market - Parasecoli, Fabio (Book collections on Project MUSE., 2017)
"Offering the first broadly comparative analysis of place-based labeling and marketing systems, Knowing Where It Comes From examines the way claims about the origins and meanings of traditional foods get made around the world, from Italy and France to Costa Rica and Thailand. It also highlights the implications of different systems for both producers and consumers. Labeling regimes have moved beyond intellectual property to embrace community-based protections, intangible cultural heritage, cultural landscapes, and indigenous knowledge. Reflecting a rich array of juridical, regulatory, and activist perspectives, these approaches seek to level the playing field on which food producers and consumers interact."--Publisher description.